2021
DOI: 10.21037/atm-21-4470
|View full text |Cite
|
Sign up to set email alerts
|

An integrated model of FTO and METTL3 expression that predicts prognosis in lung squamous cell carcinoma patients

Abstract: Background: Lung squamous cell carcinoma (LUSC) approximately accounts for a third of lung cancers.However, the role of N6-methyladenosine (m6A) in LUSC remains largely unknown according to previous studies. Methods:In this study, we investigated the mutations, copy number variants (CNVs), expression of 20 m6A RNA methylation regulators, and clinical data from The Cancer Genome Atlas-LUSC (TCGA-LUSC). These data were used for the training cohort of screening potential biomarkers. The prognostic model of m6A RN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…e risk prognosis model based on 31 methylation sites of FRGs was superior to the model based on clinicopathologic features in the prediction of 1-, 3-, 5-, and 10-year OS in LUSC. In addition, the accuracy and efficiency of this risk prognosis model were significantly superior to other published models [17,18,[27][28][29][30][31] for LUSC patients.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…e risk prognosis model based on 31 methylation sites of FRGs was superior to the model based on clinicopathologic features in the prediction of 1-, 3-, 5-, and 10-year OS in LUSC. In addition, the accuracy and efficiency of this risk prognosis model were significantly superior to other published models [17,18,[27][28][29][30][31] for LUSC patients.…”
Section: Discussionmentioning
confidence: 76%
“…In addition, the nomogram was tested by proportional hazard assumption to analyze that whether the risk score included in our model was independent prognostic indicators. To evaluate the accuracy and effectiveness of our model, 7 prognostic models of LUSC from published papers [17,18,[27][28][29][30][31] were reviewed and studied with a comparison. Net reclassification index (NRI) and integrated discrimination improvement (IDI) are the common algorithms used to assess the model in recent years [32,33].…”
Section: Construction and Test Of The Nomogrammentioning
confidence: 99%
“…Recent research has focused on the construction of such models using factors including FTO and other genes. For instance, Zhang et al developed a model, and found that a two-gene model combining FTO and METTL3 was more effective in guiding prognostic assessment of lung cancer (66). Additionally, researchers have utilized methylation-related enzymes such as FTO and ALKBH5 to develop risk assessment models for LUAD patients.…”
Section: Application Of M6a Demethylase In the Lung Cancer Prognosis ...mentioning
confidence: 99%
“…Non-small cell lung cancer (NSCLC) constitutes approximately 85% of all lung cancer cases and encompasses various histological subtypes, including adenocarcinoma, squamous cell carcinoma, and large-cell carcinoma [ 3 ]. Among these subtypes, squamous cell carcinoma accounts for approximately 30% [ 4 , 5 ]. Due to the absence of noticeable symptoms and effective screening methods, lung cancer is often diagnosed at advanced or metastatic stages, resulting in poor long-term prognosis [ 6 ].…”
Section: Introductionmentioning
confidence: 99%